Bioengineered solar harvesting systems for next generation applications. (1st January 2022) - Saxena, Shatakshi; Dixit, Fuhar; Dalapathi, Goutam Kumar; Krishnamurthy, Satheesh; Kandasubramanian, Balasubramanian
Graphical abstract: Highlights: Outlines the most tunable and scalable fabrication techniques deciphering the characteristic properties affiliated with efficient light harvesting materials (LHM). The incorporation of sequential harvesting complexes, or quantum dots with surficial absorption and excitation properties improve the future of LHM. Fusing accelerometer technology and light harnessing, we might be able to feed the accelerated electrons to an energy harvesting system or the accelerated electrons. Accelerated electrons can be used to irradiate DNA which has applications in ingestible batteries, as drug delivery vehicles and stimulants. Abstract: In light of the ever growing enthusiasm and enormous curiosity towards bioinspired strategy of material fabrication, this review compiles the milestone in the world of bio-hybrid nanomaterials featured in light harvesting systems. The change in global climate emphasizes the need for alternative energy sources, so, comprehending the characteristic properties affiliated with nature sensitive light harvesting materials (LHM) along with their scalable fabrication techniques is a major research avenue. The last few decades have seen elevated efforts in understanding photosynthetic mechanisms, energy transfer, charge storage and principles of quantum coherence. These are further applied to devise synthetic alternatives for photo-electrochemical systems. The intriguing optoelectronic abilities of narrow bandgap semiconductors and self-assembly in bio-hybrid structures have been invasively studied to yield multifarious applications in, photocatalysis, as photoelectrodes, for hydrogen generation or water desalination. Translating the principles of evolution in natural photoactive complexes, material scientists have investigated new elements resulting in synergistic - biohybrid systems. The paper facilitates the reader with state-of-the-art examples offering a solid background to fuel innovations that can be shaped into real-world applications. From photosynthetic antennas, marine sea shells to tea leaf stains and DNA assembly, the platform has housed diverse sources converging on designing efficient and stable architectures. The article advances to modules classifying the origin of artificial optoelectronic alternatives and provides a garnered account of all addressed photo physical theories. The overview proposes the design of futuristic systems that utilize artificially intelligent energy harvesting schemes to build smart devices for biomedical and environmental remediation purposes. Hereby, we aim to provoke a cross-disciplinary discussion about the challenges and scope at the leading edge of this field and pitch to develop a different world through renewable energy push.